Pengaruh Faktor Keuangan dan Faktor Non Keuangan terhadap Kinerja Pemerintah Daerah - Nadila Sundari; Fefri Indra Arza (Universitas Negeri Padang, 2021)
This study aims to provide empirical evidence about the influence of financial factors (Size,Wealth, Intergovermental Revenue, Leverage and Capital Expenditures) and non-financial factors (Population, Legislative Size, Service Period and Age of Regional Heads) on the performance of local governments in Indonesia. evaluation of the performance of local government administration (EKPPD) as the main source. The population used in this study is the district / city government in 2018 consisting of 415 districts and 93 cities in Indonesia. The research sample was taken using purposive sampling method, the total sample obtained was 39 data. The results showed that the variables size, wealth, intergovernmental revenue, leverage, capital expenditure, legislative size, tenure of regional heads and age of regional heads had no effect on local government performance, while population had an effect on local government performance in Indonesia.